2018
DOI: 10.1186/s13018-018-0727-z
|View full text |Cite
|
Sign up to set email alerts
|

Axial loading during MRI induces significant T2 value changes in vertebral endplates—a feasibility study on patients with low back pain

Abstract: Background: The function of the endplate (EP) is the most important factor influencing nutritional supply to the avascular intervertebral disc (IVD). It is desired to have a non-invasive method to assess functional EP characteristics in vivo. Assessment of functional EP characteristics is important in order to understand its relation to IVD degeneration, which in turn might deepen the understanding of the pathophysiology behind low back pain (LBP). It was hypothesized that, by comparing quantitative MRI of EPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
22
2
Order By: Relevance
“…Importantly, the difference in T2-value between groups may indicate that EPs and vertebrae in LBP patients have altered biodynamical characteristics compared to controls. Additionally, present findings support our previous study that displayed load-induced T2-effects in EPs and difference in T2-value between superior and inferior EPs [14]. Hence, alMRI may reveal functional differences in EPs between patients and controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, the difference in T2-value between groups may indicate that EPs and vertebrae in LBP patients have altered biodynamical characteristics compared to controls. Additionally, present findings support our previous study that displayed load-induced T2-effects in EPs and difference in T2-value between superior and inferior EPs [14]. Hence, alMRI may reveal functional differences in EPs between patients and controls.…”
Section: Discussionsupporting
confidence: 91%
“…Also, new functional properties of the EPs and vertebrae may be displayed when the spine is loaded during MRI (alMRI), compared to conventional MRI that is performed with the spine unloaded (uMRI). In a small cohort study, we have shown that alMRI affects EPs in patients differently than in controls [14]. At present, no work has previously studied the dynamic behaviour of Modic changes.…”
Section: Introductionmentioning
confidence: 90%
“…Subsequently, the substance transport through intervertebral discs is prevented, thus reducing the synthesis of the intervertebral disc matrix and the water content of the nucleus pulposus. This vicious cycle ultimately leads to the degeneration of intervertebral discs and varies in accordance with biomechanical functions 43 . This study showed that the T2 values of the endplates in the Pm grade I-II and III, I-II and IV-V, and III and IV-V were statistically significant.…”
Section: Relationship Between the Degree Of Disc Degeneration And T2 mentioning
confidence: 99%
“…Intervertebral discs, as the largest avascular organs in humans, mainly obtain nutrition by two pathways, including the endplate nutritional pathway and the annulus fibrous nutritional pathway [8]. As the most main nutritional pathway of the discs, the endplate nutritional pathway also plays important role in the degeneration of intervertebral disc [9, 10]. However, the effect of blocking the endplate nutritional pathway on the IDD was still unclear and controversial [5, 6].…”
Section: Discussionmentioning
confidence: 99%